HEALTH EFFECTS OF TOBACOO - Shah, S. Humayun (Journal of Ayub Medical College Abbottabad, 1989)
Tobacco in various forms has been used for centuries. American Indians were apparently the first to use tobacco in various forms: they smoked, chewed and sniffed. Tobacco plant is a native of tropical America. The original ancestor is not known because tobacco is a very old plant and has been under cultivation for centuries. The plant spread all over North America before the arrival of Whiteman. When Columbus first landed in 1492, some of the natives brought him a gift of dried leaves.’ Throughout the West Indies, Columbus found that the tobacco trade between Indian tribes had been prevalent for hundreds of years. It was found that the Indians either inhale the smoke of the leaves when set alight in pipes, cigarettes, cigars or chewed the leaf itself. Smoking and other forms of tobacco use had become a part of everyday life, and tobacco had real economic significance. In addition, it was used in the form of poultices and pastes for treating burns, sores, cancers, sciatica, diseases of the liver, spleen and womb, chills, convulsions, worms, colic, warts, corns and bites by rabid dogs. This habit was adopted by white sailors and through them reached Europe from where it spread to Africa, Australia and Asia. The practice of smoking was not very common in Europe until 1586 but from there on-ward its popularity increased inspite of opposition by Clergymen and rulers. Linnaeus in 1753, named the genus of Tobacco Plant as Nicotiana tobaccum after the French statesman Nicot. In 1828, the most important known ingredient of tobacco was isolated and called Nicotine.2 The eighteenth century was the century of smokeless tobacco (snuff and chewing tobacco). Its decline started about in 1850, when the sale of cigars and pipes began to take the lead and during the late 1800s the chewing tobacco decreased greatly, when chewing and spitting were excoriated by leaders in medicine and science such as Koch, Pasteur and Lister who associated the habit with germs and transmission of communicable diseases.3 Since the early 1970s, there has been a great resurgence in the use of all forms of smokeless tobacco in the United States. The sales of smokeless tobacco have increased about 11% each year since 1974 with an estimated 22 million users in the United States.4 In Pakistan, the annual production of tobacco amounts to 70-80 million kg of which 85% is consumed within the country in various forms (smoking, chewing, nasswar and hooka). Over 80% of the country’s smokers are males aged 15 and above whereas smoking among females in relatively uncommon